Translation and Content Validation of the Self-Administered Version of the International Restless Leg Syndrome Severity Scale (sIRLS) - Syifanaurah, Salma; Anna, Anastasia; Eryani, Theresia (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Restless Legs Syndrome (RLS) is a neurological sensorimotor disorder that causes a person to feel the need to move their lower extremities due to uncomfortable sensations. This condition can be monitored to minimize and cure the symptoms. One of the monitoring instrument is The Self-administered version of The International Restless Legs Syndrome Rating Scale (sIRLS). In Indonesia, the sIRLS instrument has not been culturally adapted. This research aims to translate and to test the content validity the Indonesian version of the sIRLS, so that it can further contribute to subsequent psychometric research on this instrument. Methods: The sIRLS were translated through forward translation, synthesized translation, back-translation, synthesized back-translation, and expert committee by five translators and three expert judges. Content validity was tested through CVR, I-CVI, and S-CVI for the essentiality, relevancy, and clarity of each item. Results: The first validity test showed a significant value for essentiality and relevancy of all the items (1,00). However the first test showed an insignificant value for the clarity of the seven items (0,33 and 0,66). Therefore the researcher should revise the seven items based on the suggestions from the expert judges and then carry out a second content validity test. Consequently, the final values of the CVR, I-CVI, and S-CVI showed significant values (1,00) for the essentiality, relevancy, and clarity. Discussions: Many Adaptation and modification on a few terms were required to achieve both meaning and cultural equivalence and also to facilitate understanding of the respondents. Conclusion: The Indonesian Version of self-administered version of The International Restless Legs Syndrome Rating Scale (sIRLS) is validly reviewed from the essentiality, relevancy, and clarity of the items.